Peran Kode Etik Atas Pengaruh Akuntansi Forensik, Audit Investigatif dan Data Mining Terhadap Pendeteksian Dugaan Tindak Pidana Pencucian Uang - Tri Puji Raharjo; Syahril Djaddang; Edy Supriyadi (Magister Akuntansi Universitas Pancasila, 2020)
ABSTRACT This research aims to examine and analyze the effect of forensic accounting, investigative audit and data mining on detection of criminal act of money laundering’s suspicion with the role of ethics code as a moderating factor. The research object are the analyst and examiner of financial transaction of a governmental institution named Pusat Pelaporan and Analisis Transaksi Keuangan (Indonesian Financial Transaction Report and Analysis Centre) with a total of 40 respondents. This research is using nonprobability sampling method. Data analysis is performed using Stuctural Equation Modeling Partial Least Square (SEM-PLS) by using WarpPLS 6.0. The results showed that forensic accounting has significant effect, investigative audit doesn’t have effect and data mining doesn’t have effect on criminal act of money laundering’s suspicion. The role of ethics code moderates the effect of investigative audit on the detection of criminal act of money laundering’s suspicion and also moderates the effect of data mining on the detection of criminal act of money laundering’s suspicion. The contribution of this research is strengthening and enriching the source of information about the scope of forensic accounting’s implementation. ABSTRAK Tujuan penelitian ini adalah menguji dan menganalisis pengaruh akuntansi forensik, audit investigatif dan data mining terhadap pendeteksian dugaan tindak pidana pencucian uang dengan peran kode etik sebagai variabel pemoderasi. Objek penelitian ini adalah analis dan pemeriksa transaksi keuangan pada Pusat Pelaporan dan Analisis Transaksi Keuangan sebanyak 40 orang. Metode sampling yang digunakan adalah nonprobability sampling. Metode analisis data pada penelitian ini adalah Stuctural Equation Modeling Partial Least Square (SEM-PLS) menggunakan WarpPLS 6.0. Hasil penelitian ini adalah akuntansi forensik berpengaruh signifikan, audit investigatif tidak berpengaruh dan data mining tidak berpengaruh terhadap pendeteksian dugaan tindak pidana pencucian uang. Peran kode etik memoderasi pengaruh audit investigatif terhadap pendeteksian dugaan tindak pidana pencucian uang dan juga memoderasi pengaruh data mining terhadap pendeteksian dugaan tindak pidana pencucian uang. JEL Classification : M48, M40